Moringa seed extract with a potential similar flocculant activity to a synthetic polymer during sugarcane clarification - Teixeira, Vitor [UNESP]; Parra, Silvia Cristina Marques [UNESP]; Silva, Aline Ferreira [UNESP]; Costa, Gustavo Henrique Gravatim; de Freita, Lidyane Aline [UNESP]; de Freita, Cristhyane Millena; Mutton, Márcia Justino Rossini [UNESP] (My University, 2021)
Synthetic polyelectrolytes made from acrylamide are used as flocculants in the sugarcane juice clarification process, which is neurotoxic and has carcinogenic properties. As supposed, the synthetic polymer could result in residue in the sugar. However, it has no information in the literature and either can be used in organic production systems. Thereafter, the goal of this research is to evaluate the use of Moringa oleifera seed extract in different salt solutions as a natural substitute for the synthetic flocculant currently in use. The experimental design was completely randomized with 6 treatments; moringa extracts in 1 M saline solution of NaCl, KCl, CaCl2, H2O, and synthetic polyelectrolyte (Magnafloc); and control (no flocculant addition). Turbidity analysis shows that the synthetic polymer removes 87.8% of the impure particle in the juice and the extract based on CaCl2 with 79.1%; the clarification of the impurities has the same particle sedimentation rate of 3.74 cm min−1, concluding the moringa extract in saline solution of CaCl2 1 M in the concentration of 100 mg L−1 presents a similar activity as the synthetic polymer.
Keywords: Clarification; Moringa oleifera Lamarck; Polyelectrolytes; Sedimentation; Simple defecation; Sugar